Acute kidney injury electronic alerts: mixed methods evaluation of their implementation into secondary care, utilising normalisation process theory. (2019) - Scott, Jason; Finch, Tracy; Maniatopoulos, Gregory; Bevan, Mark; Kanagasundaram, Suren
No abstract available